The Development of Pineapple Leave Fibre Composite Material for Marine Application Using Hand Lay-Up Method - majibul rahman, muhammad iqmal aizat; Ariffin, Ahmad Hamdan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Pineapple leaf fiber (PALF), abundant in Malaysia, holds potential for industrial use, particularly in reinforcing materials. This study focuses on utilizing PALF as reinforcement with epoxy for marine applications. The research explores the impact of layering, orientation, and material volume on flexural strength and water absorption. Samples, composed of 3 layers with 70% epoxy and 30% PALF, undergo a 3-point bending flexural test, evaluating maximum force, stroke, stress, strain, and Young's modulus. Water absorption and SEM analysis complement the study. Results highlight the uni-directional configuration's superior mechanical properties, with the highest flexural strength (735.52 N), ultimate tensile strength (16.17 MPa), and Young's modulus (0.0054 MPa). Notably, the uni-directional sample exhibits excellent water resistance, outperforming multi-directional and inclined directional counterparts. These findings emphasize the promising potential of PALF-epoxy composites for marine applications.